2022
DOI: 10.3389/fpsyt.2022.909947
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the WHO caregivers skills training program with caregivers of autistic children via telehealth in rural communities

Abstract: BackgroundFor families with autistic children living in rural areas, limited access to services partly results from a shortage of providers and extensive travel time. Telehealth brings the possibility of implementing alternative delivery modalities of Parent Mediated Interventions (PMIs) with the potential to decrease barriers to accessing services. This study aimed to evaluate the feasibility and acceptability of implementing the World Health Organization-Caregivers Skills Training program (WHO-CST) via an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 82 publications
(119 reference statements)
3
7
0
Order By: Relevance
“…In our study we report lower ratings of caregiver participation in virtual CST compared to in-person CST, mirrored by qualitative findings of emotional distance and impotence perceived by facilitators and caregiver difficulties in creating meaningful relationships in virtual CST. These findings are in line with those of Montiel-Nava et al ( 2022 ), who reported that parents receiving CST remotely in rural Missouri seemed more focused understanding the content than in sharing experiences with other parents, and of Taylor et al ( 2021 ), who reported greater reluctance to ask questions, participate in group discussions and connect with other participants in parents enrolled in an online parent training than in those receiving the corresponding in-person training. However, it is important to consider that our findings may also have been affected by emotional reactions to isolation during the pandemic.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study we report lower ratings of caregiver participation in virtual CST compared to in-person CST, mirrored by qualitative findings of emotional distance and impotence perceived by facilitators and caregiver difficulties in creating meaningful relationships in virtual CST. These findings are in line with those of Montiel-Nava et al ( 2022 ), who reported that parents receiving CST remotely in rural Missouri seemed more focused understanding the content than in sharing experiences with other parents, and of Taylor et al ( 2021 ), who reported greater reluctance to ask questions, participate in group discussions and connect with other participants in parents enrolled in an online parent training than in those receiving the corresponding in-person training. However, it is important to consider that our findings may also have been affected by emotional reactions to isolation during the pandemic.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, virtual CST was found to be feasible and accept to caregiver and facilitators, in line with several previous studies that evaluated the acceptability of online parent training interventions for ASD (Baharav & Reiser, 2010 ; Bearss et al, 2018 ; Dai et al, 2021 ; Ingersoll & Berger, 2015 ; Lau et al, 2022 ; Montiel-Nava et al, 2022 ; Pi et al, 2021 ; Pickard et al, 2016 ; Sengupta et al, 2021a ; Tsami et al, 2019 ; Vismara et al, 2018 ; Wainer et al, 2021 ). The online adaptation of CST was delivered with high levels of observer-rated competency and integrity, not differently from the in-person CST.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the last decade, telemedicine [ 14 ] has enriched parent-mediated early interventions [ 15 ]. Several studies, conducted on a variety of treatment models in children and adolescents with ASD, demonstrated that remote interventions are able to promote parent’s learning and caregiving skills, support a reduction of children’s behavioral problems, and contribute to an improvement in autism symptoms’ severity, language, and adaptive skills [ 16 , 17 , 18 ]. Furthermore, a few studies compared tele-assisted interventions with in-person treatments, suggesting a comparable [ 19 ] or even better outcome of the remote program.…”
Section: Introductionmentioning
confidence: 99%